Robust adaptive parameter estimators in arrhythmia detection - Clarkson, P M; Fan, Q; Williamson, G A; Arzbaecher, R (Journal of electrocardiology, 1992)
The authors consider the statistical analysis of threshold crossing intervals, as applied to estimation of tachycardia rates from intracavitary electrograms. The authors developed a class of robust algorithms designed to produce minimum variance estimates for tachycardia rates. The authors formulated the algorithms using order statistic filters, and obtained the minimum variance unbiased order statistic estimator. The potential gain in efficiency achieved by this approach is demonstrated via a representative example. The results indicated that the order statistics operator can produce dramatic reductions for typical errors in error variance as compared to linear estimators.